2017
DOI: 10.5812/sdme.68140
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Attitude of Undergraduate Students of Golestan University of Medical Sciences Towards Cheating in Exams

Abstract: Background and Objectives: Cheating is a common phenomenon that can undermine the credibility of university tests and certificates. Cheating is a more sensitive issue among medical students. The present study was conducted to investigate the performance and attitude of undergraduate students of Golestan University of Medical Sciences in Iran towards cheating, as well asthe factors that influence cheating. Methods: The present descriptive analytical and cross-sectional study was conducted in 2014 on 524 female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the study by Sanagoo et al, the discrimination coefficient of all 12 tests was low, and the highest discrimination power was 0.32 (1). The discrepancies between the mentioned findings could be due to the different nature of the studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the study by Sanagoo et al, the discrimination coefficient of all 12 tests was low, and the highest discrimination power was 0.32 (1). The discrepancies between the mentioned findings could be due to the different nature of the studies.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is impossible to distinguish between weak and strong students without observing the structural rules and the appropriate taxonomy level in designing these questions. Low-quality test also reduces learners' motivation, and teachers' and the educational system's efforts will be wasted (1). On the other hand, the type and quality of the test affect the teaching method and the teacher's credibility.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, much attention has been given to the topic of happiness in the fields of science and research (1). For human beings, happiness is considered as one of the most fundamental necessities of mental health (2). Happiness has several basic dimensions: the emotional dimension, i.e., whether the person is in a joyful and contented mood, the social dimension, i.e., whether the person has good social relations and can receive support from others, and finally, the cognitive dimension, whether the person processes and interprets information in a special way, ultimately feeling happy and optimistic.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the teaching methods employed by most faculty members often urge students to take notes in the class (5). In a study in this regard, it was reported that the large volume of educational materials, the need for time, lack of motivation to study, lack of training on different levels of education, inadequacy of available resources in the library, and large volumes of reference books are the factors that highly influence the tendency of students to using pamphlets rather than textbooks (6).…”
Section: Introductionmentioning
confidence: 99%